2019
DOI: 10.3390/ma12223692
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Modelling of the Hysteresis Loops and Strain–Energy Density for Low-Cycle Fatigue-Life Predictions of the AZ31 Magnesium Alloy

Abstract: Magnesium is one of the lightest metals for structural components. It has been used for producing various lightweight cast components, but the application of magnesium sheet plates is less widespread. There are two reasons for this: (i) its poor formability at ambient temperatures; and (ii) insufficient data on its durability, especially for dynamic loading. In this article, an innovative approach to predicting the fatigue life of the AZ31 magnesium alloy is presented. It is based on an energy approach that li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…AZ31 alloy showed cyclic softening at 150 C in the tensile region of the hysteresis loop whereas cyclic hardening was observed in the tensile region at room temperature tests in previous studies. [21][22][23] On the contrary, cyclic hardening was obtained in the compressive region of the hysteresis loop at 150 C which corresponded to the observations at room temperature [21][22][23] (Figure 8A).…”
Section: Resultssupporting
confidence: 78%
“…AZ31 alloy showed cyclic softening at 150 C in the tensile region of the hysteresis loop whereas cyclic hardening was observed in the tensile region at room temperature tests in previous studies. [21][22][23] On the contrary, cyclic hardening was obtained in the compressive region of the hysteresis loop at 150 C which corresponded to the observations at room temperature [21][22][23] (Figure 8A).…”
Section: Resultssupporting
confidence: 78%
“…Fatigue life prediction using strain‐energy density approaches has been studied by several researchers, 17,18,23,37,43,44 and is essential in the case of strain‐controlled fatigue tests, as the plastic strain amplitude plays a dominant role in determining fatigue behavior, including the nature of fatigue damage. Wang et al 17,23 proposed a strain‐energy density expression for Al–Si hypereutectic piston alloy fatigued at room and elevated temperatures, considering the concept of accumulated damage, and found that the expression was linked to fatigue life ( N f ) nicely.…”
Section: Discussionmentioning
confidence: 99%
“…In applications that use aluminium alloys frequently, it is necessary to understand the fatigue performance of the components and the effects of operating parameters on the fatigue behaviour of the analysed constructional components. A fatigue assessment can be carried out using the stress–life (S–N) or the strain–life approach, depending on whether stresses in the critical cross-sections of the analysed component are in the elastic or plastic areas [ 15 , 16 ]. In the case that only elastic stresses occur, the S–N approach is usually used to obtain the fatigue life up to the final failure of the component.…”
Section: Introductionmentioning
confidence: 99%